I'M GAY! SO WHAT? - Reina, Fabio Tadeu [UNESP]; Scabello Volpe, Alexandre Alberto (Fundacao Univ Tocantins, 2020)
The sport most of the time has its representatives fixed in the masculinity. Any and all movement contrary to this logic subverts the order and installs or precedes it beyond sex, obstructing many individuals to a professional, for assuming an opposite posture as advocated as an ideal of virility. Thus, this objective article points out and analyzes how four volleyball athletes took on homosexuality is not related to the sport itself, but that it does become a barrier for the higher level sport hierarchy, it restricts the teams that compete in the second level events, without national or international projection, because in this context its acceptance is greater.
Keywords: Sport; Gender; Homosexuality; Volleyball